Purification and properties of porcine platelet-derived growth factor. - Stroobant, P (1984)
The purification to homogeneity of a potent growth factor from porcine platelets is described. This cationic mitogen is named porcine platelet-derived growth factor (PDGF) on the basis of close structural, functional and immunological similarities to human PDGF. Porcine PDGF, like its human homologue, is a hydrophobic, disulphide cross-linked protein, which is stable to heat, acid, sodium dodecyl sulphate (SDS), and guanidine. The purified protein has an apparent mol. wt. on SDS-polyacrylamide gels of 38 000, similar to those reported for human PDGF (27 500-35 000). Amino terminal sequence analysis of native porcine PDGF gave a single 15 amino acid residue sequence, of which 11 residues were identical to the amino terminal sequence of the B chain of human PDGF. Gel permeation h.p.l.c. in guanidine solutions of the reduced protein revealed a single species of mol. wt. 17 000 suggesting that native porcine PDGF may be a homodimer of a 17 000 mol. wt. chain. Since porcine PDGF can be purified at low cost from large quantities of fresh platelets, it provides an alternative source of PDGF for structural and functional studies, and could be of use in preparing defined media for cell culture.